"Sex? no, thanks" the lived experiences of selected self-identiying asexual Filipinos. - Ligahon, Zenell Winniejoy B. (2019.)
This phenomenological study focused on exploring the lived experiences of asexual-identifying Filipinos. Data were collected from semi-structured interviews of seven (7) participants, six females and one male currently residing in the Philippines who have undergone recruitment and screening process through the Asexual Identification Scale (AIS). The gathered data from these interviews were analyzed through the process of Interpretative Phenomenological Analysis (IPA). Findings of this study revealed that asexual Filipino experience is complex and multi-faceted. Four main factors have been identified that influence their lived experiences: (1) self-identification as an asexual, (2) romantic orientation, (3) personal preferences, (4) cultural expectations. In summary, the various dimensions of their identity and sexual orientation is compounded by the Philippine social climate regarding asexuality which is characterized by heteronormativity, lack of awareness and adherence to cultural and traditional beliefs and norms. These findings could contribute to better understanding of asexuality in the Philippines and it may be relevant to explore experiences of married asexual, aromantic and romantic asexual and other identities under the asexuality umbrella for future research.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Asexuality -- Philippines